Physicochemical, Phytochemical, and Antioxidant Properties of Spent Hops from Craft Beer Brewing - Musika, Sumalee; Khongla, Chompoonuch; Samsalee, Namfon; Bumrungpakdee, Thidarat; Dunkhunthod, Benjawan (Trends in Sciences, 2025)
Spent hops, a byproduct of brewing exhibit interesting functional qualities and antioxidant potential. This study aimed to determine the physicochemical, phytochemical, and antioxidant characteristics of dried spent hop (DSH) obtained from Weizen craft beer brewing. Additionally, spray-dried spent hop powder (DSH-SD) was examined. GC-MS analysis revealed that the major components of DSH powder were propanoic acid, 3,3’-thiobis-, didodecyl ester (19.64%), and dodecyl acrylate (15.95%). The DSH exhibited a moisture content of 5.85 ± 0.05%, ash content of 4.53 ± 0.01%, protein content of 14.81 ± 0.60%, and water activity (aw) of 0.3182 ± 0.01. Based on phenolic and flavonoid contents, as well as antioxidant activities evaluated through the ABTS and FRAP assays, the optimal extraction condition for spray drying was determined to be 80 °C for 60 min. After spray drying, DSH-SD exhibited a moisture content of 8.39 ± 0.10%, ash content of 2.52 ± 0.23%, protein content of 3.88 ± 0.17%, and aw of 0.4460 ± 0.01. DSH-SD had a total phenolic content of 13.17 ± 0.62 mg GAE/g and a total flavonoid content of 4.10 ± 0.14 mg CE/g. The antioxidant activity was 20.17 ± 0.77 mg TE/g (ABTS assay) and 19.09 ± 1.46 mg TE/g (FRAP assay). DSH-SD showed fair flowability with a Carr index of 17.09 ± 1.48%, tapped density of 0.31 ± 0.00 g/cm³, and bulk density of 0.26 ± 0.00 g/cm³. These findings suggest that DSH-SD is a promising, sustainable ingredient for functional food applications with potential health benefits. HIGHLIGHTS Dried spent hops (DSH) were analyzed for their physicochemical, phytochemical, and antioxidant properties. GC-MS of DSH revealed key bioactive compounds, including propanoic acid derivatives and dodecyl acrylates. The optimal extraction condition for spray drying DSH at 80 °C for 60 min enhanced the highest phenolic and flavonoid contents, with strong antioxidant activity. Spray-dried DSH (DSH-SD) exhibited antioxidant activity and fair flowability, making it a viable functional food ingredient. GRAPHICAL ABSTRACT